Rapid diagnostic tests to detect asymptomatic malaria in primary health care facilities in hypoendemic areas - Siahaan, Lambok; Alrasyid, Harun; Akbari, Ratna; Eyanoer, Putri; Panggabean, Merina; Panggabean, Yoan (Family Medicine & Primary Care Review, 2016)
Background. Early detection and appropriate treatment of malaria, as well as elimination of vectors, will prevent the transmission of the disease. Nowadays, malaria treatment is only administered after the illness has been laboratory confirmed using, e.g., rapid diagnostic tests (RDTs), when microscopy is not available. RDTs are commonly used in patients reporting to primary health care (PHC) providers with a fever. If left untreated, asymptomatic malaria could be a source of disease transmission and may potentially lead to an outbreak. Yet, the detection of asymptomatic malaria is difficult, as parasitological tests are only performed in symptomatic patients, i.e. those presenting with a fever. Objectives. The aim of the study was to assess the rates of asymptomatic malaria cases in hypoendemic areas. Malaria was detected through RDTs that were performed at PHC facilities in the Batubara District in the North Sumatera Province in Indonesia. Material and methods . Data was collected from two PHC providers and four villages with the highest rate of malaria cases. Malaria was diagnosed based on RDTs and then confirmed by microscopic examination, which remains the gold standard. Results. The study group included 504 patients. The overall sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of the RDTs for the diagnosis of any malarial species were 77.9%, 41.9%, 59.4% and 63.5%, respectively. The proportion of asymptomatic malaria was 22.1%. Asymptomatic malaria cases were mainly due to Plasmodium vivax. Conclusions . Periodic mass blood surveys are necessary to identify asymptomatic malaria cases in hypoendemic areas.